Textile choreographies: body, memory and educational knowledge (Revista Apotheke, 2025)
In this section of the research “Textile Choreographies: Body, Memory and Knowledge in the Living Weave of Artist Teaching”, we explore the interconnection between the body, textile practice and teaching of visual arts. The emphasis is on the gestures inherent to textile practices conceived as bodily performances that transcend the technical execution itself to an indispensability that is relational and integrative for the human being. In addition to analyzing these gestures in themselves and in our creative processes, we will investigate their educational implications, through the repetition, undoing, mending and joining of threads, lines, needles and fabrics in the textile work “NÓS, DE MUITAS”, which consists of the collective sewing of a quilt and reveals specific nuances about educational knowledge for contemporary times. Textile processes are an invitation to collectivization, just as threads that intertwine to form a weft, the encounters mediated by textiles create networks of belonging and learning. In formal and informal spaces, textile making becomes a territory for listening and experimentation, a place where time is plural and learning takes place through engagement with the sensitive.
Keywords: textile art; visual art; body; education